2011
DOI: 10.1590/s0100-29452011000500042
|View full text |Cite
|
Sign up to set email alerts
|

Pós-colheita de mangas 'Tommy Atkins' recobertas com quitosana

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a influência de cobertura de quitosana na pós-colheita de mangas 'Tommy Atkins', colhidas "de vez" e armazenadas a 23 ºC (65% UR). As mangas foram adquiridas na CEAGESP de Ribeirão Preto-SP, e transportadas ao Laboratório de Tecnologia de Produtos Agrícolas da UNESP de Jaboticabal. Após a seleção, os frutos foram higienizados em solução de dicloro s. triazinatriona sódica di-hidratada (Sumaveg ® ) a 200 mg 100g -1 de cloro livre por 10 minutos, secadas, imersas nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 14 publications
2
15
0
13
Order By: Relevance
“…Souza et al (2011), who coated 'Tommy Atkins' mangoes with chitosan, also found that the coating used could delay the development of fruit color and thus the ripening of mangoes.…”
Section: Resultsmentioning
confidence: 99%
“…Souza et al (2011), who coated 'Tommy Atkins' mangoes with chitosan, also found that the coating used could delay the development of fruit color and thus the ripening of mangoes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was verified that the lowest contents occurred in mangoes not treated with the extract (control), with significant differences from treatments with A. nodosum ( Figure 4D). This is an indication that treatments with seaweed extract decelerate the normal process of senescence of mangoes, since the decrease in fruit acidity is associated to the consumption of acids in the respiratory process, due to maturation (CHITARRA;CHITARRA, 2005;SOUZA et al, 2011). As in previous trials, linear regression analysis showed that the titratable acidity is much more related to the storage time and consequent fruit ripening (R 2 = 0.98), than to concentrations used in the tests (R 2 = 0.36) ( Figures 4E and 4F).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have documented the potential of certain commercially available substances and products in the protection of mangoes and in the improvement of the physiological quality of fruits (AMARIZ et al, 2010;PLOTTO et al, 2010;SOUZA et al, 2011). Many other products are available; however, few have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…O escurecimento pós-colheita é resultado de um processo geralmente atribuído à degradação dos pigmentos vermelhos (antocianinas), associado com a oxidação de compostos fenólicos pelas enzimas polifenoloxidase (PPO) e/ou peroxidase (POD) (SOUZA et al, 2011).…”
Section: Introductionunclassified
“…Tem sido muito empregada em tratamentos de pós-colheita, pois apresenta propriedade "filmogênica", formando uma camada protetora sobre os frutos imergidos em suas soluções, auxiliando na redução da perda de água, modificando a atmosfera e reduzindo o amadurecimento dos frutos (SOUZA et al, 2011). Essas propriedades vêm sendo observadas em diversas frutas, como longans (JIANG; LI, 2001), lichias (HOJO et al, 2011), mangas (SOUZA et al, 2011, dentre outras.…”
Section: Introductionunclassified